Update Management of Atopic Dermatitis - Sari, Indri Widya; Diba, Sarah; Nopriyati; Athuf Thaha; Raden Pamudji; Fitriani (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Atopic dermatitis (AD) is a chronic recurrent skin disease that is very complex due to impaired skin barrier function in the form of xerosis, chronic eczematous lesions, and itching, commonly found in infants and children. Pathogenesis is thought to be the interaction of genetic factors, immune dysfunction, epidermal barrier dysfunction, and the role of the environment and infectious agents. Approach the disease by performing etiopathogenesis algorithms, clinical manifestations, diagnosis, and treatment. Based on the 2013 Asia-Pacific consensus, AD management guidelines using the 5-pillar principle have long been used. Currently, the European consensus in 2018 has developed new guidelines for AD management. Purpose: To provide an updated treatment for AD. Review: The ethiopathogenesis of AD is influenced by genetics, skin barrier disorders, and immune response disorders. Updated management of the European consensus in 2018 includes education, avoidance of precipitating factors, psychosomatic counseling, optimization of skin barrier function with moisturizers, anti-inflammatory and antimicrobial administration, allergen-specific immunotherapy, complementary and alternative drugs, phototherapy, and controlling the itch-scratch cycle with anti-itch in pediatric and adult AD patients. AD may affect patients’ quality of self-esteem. In general, patients expect higher. Conclusion: AD affects the psychosocial aspects of patients. Updated management of AD adequately improves the quality of life.